Comparison of psychological factors between healthy athletes and those suffering from chronic ankle instability - San Antolín Gil, M; Ceballos Laita, L; Jiménez Del Barrio, S; Calvo Lobo, C; Rodríguez Sanz, D; Llamas Ramos, R; Llamas Ramos, I; García García, D. (Journal of Human Sport & Exercise, 2025)
Background: Ankle sprain is the most common traumatic injury among handball players, which usually leads to the development of Chronic Ankle Instability (CAI). There is much evidence regarding the mechanical component about this condition; however, the psychological component has been little studied in previous research. The aim of this study was to compare anxiety, personality traits, depression, and kinesiophobia between young handball players with and without CAI.